Genetic and biomarker approaches to uterine fibroids: toward precision medicine - Mukherjee, Pooja (Frontiers in Global Women's Health, 2025)
Uterine fibroids (UFs) are the most common benign tumors of the female reproductive system, affecting 70%–80% of women by age 50. Early detection is challenging due to the absence of initial symptoms, and diagnosis primarily relies on ultrasound and magnetic resonance imaging (MRI). However, biomarker-driven approaches could enable earlier and more precise detection. This review explores emerging biomarkers and genetic factors in fibroid pathogenesis. Potential biomarkers, including PLP1, FOS, versican, LDH, and IGF-1, show promise for diagnosis and recurrence prediction. Genetic studies have identified key mutations in MED12, FH, HMGA2, and COL4A5-COL4A6, alongside genome-wide association studies (GWAS) that highlight fibroid risk loci. Interestingly, biomarkers may also be mutation-type specific, suggesting potential for more precise molecular classification. Gene therapy offers an innovative treatment approach but the genetic landscape of fibroids remains underexplored, limiting advancements in research and funding. Integrating biomarker-based diagnostics and genetic profiling could transform fibroid detection and management, reducing reliance on invasive procedures. This review highlights the urgent need for improved diagnostic tools, prognostic markers, and targeted therapies for uterine fibroids.